Global Journal for Research Analysis 2022
DOI: 10.36106/gjra/4900524
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Study of Abdominal Wound Dehiscence

Abstract: INTRODUCTION:-AWD (abdominal wound dehiscence) is a word that is widely used to describe the separation of different layers of an abdominal wound before it has healed completely. Acute laparotomy wound failure and burst abdomen are two more words that are used interchangeably. Wound dehiscence happens when a wound does not develop the necessary strength to withstand the demands exerted on it. Dehiscence happens when sutures are disrupted by external pressures, absorbable sutures dissolve too quickly, or tight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In the current study, other methods of prevention of SSIs, like antibiotic cover and control of blood sugar levels, were kept similar in both groups. 30 A wound-closure review suggested removing dressings after 48 hours, 31 but all subjects in the current study underwent dressing for 7 days. The dressings were used in I&S group to create a seal for continuous suction and to approximate the stitched abdominal wall closer to the rectus sheath after removal of the drains.…”
Section: Discussionmentioning
confidence: 92%
“…In the current study, other methods of prevention of SSIs, like antibiotic cover and control of blood sugar levels, were kept similar in both groups. 30 A wound-closure review suggested removing dressings after 48 hours, 31 but all subjects in the current study underwent dressing for 7 days. The dressings were used in I&S group to create a seal for continuous suction and to approximate the stitched abdominal wall closer to the rectus sheath after removal of the drains.…”
Section: Discussionmentioning
confidence: 92%